From Language Learning to Multiliteracies: Exploring Digital Literacy and Student Skill Development in Indonesian for Foreign Learners - Sholikhah, Hani Atus; Ernalida, Ernalida; Izzah, Izzah; Putri, Astrid Yulinda; Nuzula, Khalidatun (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study explores the integration of digital literacy into BIPA (Bahasa Indonesia bagi Penutur Asing—Indonesian for Foreign Learners) instruction as a strategy to promote the comprehensive skill development of international students, encompassing linguistic, digital, and intercultural competencies. Employing a corpus-based qualitative approach, the research focuses on the analysis of authentic digital communication products created by foreign students through task-based learning activities. The corpus consists of multimodal texts—including blog entries, podcast transcripts, infographics, and interactive digital posters—collected from intermediate-level BIPA students at universities at South Sumatra. The findings reveal three key insights. First, linguistically, students demonstrate improvements in sentence structure, thematic vocabulary (culture, society, technology), and pragmatic appropriateness in digital contexts. Second, in terms of digital literacy, students effectively utilise various platforms (Padlet, Canva, and Flipgrid) to construct and deliver messages creatively, interactively, and in alignment with audience expectations. Third, interculturally, students exhibit the ability to interpret local communication norms, avoid cultural faux pas, and present cross-cultural perspectives through their digital narratives. Corpus analysis also indicates a shift in learners’ roles—from passive recipients of information to reflective, collaborative, and globally connected content creators. This study highlights the potential of integrating digital literacy into BIPA instruction to foster essential 21st-century competencies. The findings provide a valuable foundation for developing a BIPA curriculum that is responsive to both digital transformation and the cultural diversity of international students.